APLIKASI ABU SEKAM PADA KONDISI DIBAWAH KAPASITAS LAPANG PADA LIMA VARIETAS PADI GOGO: HASIL DAN KOMPONEN HASIL - Ahadiyat Yugi Rahayu; Tri Harjoso (Universitas Trunojoyo Madura, 2010)
Objective of the study was to know application of burned-rice husk under lower soil field capacity on yield and yield components. The pot study was done at wire house Faculty of Agriculture Jenderal Soedirman University. Randomized complete block design was applied with the factors of variety (Situ patenggang, Limboto, Towuti, Batutegi dan Aek sibundong) and burned-rice husk (0, 2, 4, 6 t/ha), and three times replication. The result showed that application of burned-rie husk up to 6 t/ha could not improve yield and yield component at all varieties. Towuti and Aek sibundong varieties resulted the higher numbers of tiller and panicle, and weight of grain wth the values of 38,8 and 41,8; 26,31 and 27,71; 36,06 and 37,24 g, respectively. Aek sibundong had a highest value of 1000 seeds weight of 25,09 g. Batu tegi resulted the highest value on panicle length and, number of grain per panicle and per pot of 23,62; 206,71 and 2540,58, respectively